Comment on COVID‐19 in patients with myasthenia gravis: Author response. Issue 6 (21st September 2020) - Anand, Pria; Slama, Michaël C. C.; Kaku, Michelle; Ong, Charlene; Cervantes‐Arslanian, Anna M.; Zhou, Lan; David, William S.; Guidon, Amanda C.
Abstract : See article on pages E85–E86 in this issue .